Unravelling the Synthesis of Benzo[d]imidazo[2,1-b]thiazoles via MnO2/I2-Catalyzed Ortoleva-King Type Approach - Aneeja, Thaipparambil; Saranya, Padinjare Veetil; Anilkumar, Gopinathan (Synlett, 2025)
The first MnO2/I2-catalyzed one-pot synthesis of benzo[d]imidazo[2,1-b]thiazole from 2-aminobenzothiazole and aryl methyl ketone has been described. This methodology involves the in situ generation of α-iodoketone from aryl methyl ketone in the presence of a catalytic amount of molecular iodine. An array of aromatic ketones and 2-aminobenzothiazoles were compatible with this strategy, providing diverse fused benzoimidazothiazoles in moderate to good yields.
Keywords: Benzo[d]imidazo[2,1-b]thiazole; Aryl methyl ketone; 2-Aminobenzothiazole; Ortoleva-King type reaction; Manganese; Iodide source